2008
DOI: 10.1158/1078-0432.ccr-08-0358
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Report of a Radiation Dose-Escalation Trial in Patients with One to Five Sites of Metastatic Disease

Abstract: Purpose: Previous investigations have suggested that a subset of patients with metastatic cancer in a limited number of organs may benefit from local treatment. We investigated whether cancer patients with limited sites of metastatic disease (oligometastasis) who failed standard therapies could be identified and safely treated at one to five known sites of low-volume disease with radiotherapy. Experimental Design: Patients with one to five sites of metastatic cancer with a life expectancy of >3 months and good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 28 publications
3
78
2
Order By: Relevance
“…The European Society for Medical Oncology states that oligometastases are defined as at maximum five metastatic lesions in the body (8). However, some studies found that patients with 1 or 2 lesions had significantly better survival than those with 3 to 5 metastatic lesions (9). In our study, the OS of patients with two lesions in a single organ was not statistically inferior to OS of patients with a single lesion in a single organ (P=0.180).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The European Society for Medical Oncology states that oligometastases are defined as at maximum five metastatic lesions in the body (8). However, some studies found that patients with 1 or 2 lesions had significantly better survival than those with 3 to 5 metastatic lesions (9). In our study, the OS of patients with two lesions in a single organ was not statistically inferior to OS of patients with a single lesion in a single organ (P=0.180).…”
Section: Discussioncontrasting
confidence: 54%
“…One of the possible explanations for this result is that in our study 70% of patients with multiple metastases in a single organ had 5 or less metastases. According to some authors, this could be considered oligometastases and could be associated to a better prognosis (8,9). This finding of our study raises the question whether patients with few metastases in a single organ should be included in M1c category.…”
Section: Discussionsupporting
confidence: 50%
“…This may also explain why repeated radiotherapy is less immuno-supportive than a single dose (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The recent advances in radiotherapy allow the use of high-dose irradiation as part of stereotactic radiotherapy while minimizing adverse side effects. Clinical evidence shows that patients treated with one to two high doses of radiotherapy respond better than those treated with fractionated low-dose radiotherapy, and the involvement of other mechanisms than direct killing of tumor cells has been suggested (15)(16)(17)(18). It was shown recently that single highdose radiotherapy but not fractionated low-dose radiotherapy increased accumulation of CD8 + T cells in the tumor (19), crucially depended on CD8 + T cells (20), and resulted in the generation of tumor-specific CTLs (21).…”
mentioning
confidence: 99%
“…In some selected lung cancers, or limited forms of metastasis, very large doses (one to five treatments of 10-20 Gy) may be used (1). Despite research into the radiobiology and physics of radiotherapy, many patients fail within the irradiated target volume.…”
Section: Introductionmentioning
confidence: 99%